Electro Cardiographic Features of Ptients With Tetralogy of Fallot - Al-Hamash, Sadiq M.; Al-Rubaiy, Fadhil; Hassan, Dhia’a (AL-Kindy College Medical Journal, 2007)
Background: For many decades, the ECG was theworkhorse of non-invasive cardiac test and today althoughother techniques provide more details about the structuralanomalies in congenital heart diseases, ECG is likely to bepart of clinical evaluation of patients with such diseasesbecause it is inexpensive, easy to perform and in certainsituations may be both sensitive and specific.Objective: this study carried out to identify the pattern ofECG study in patients with TOF.Methods: this is a retrospective study of 200 patientswith TOF, referred to Ibn Al-Bitar cardiac center fromApril 1993 to May 1999. The diagnosis of TOF establishedby echocrdiographic, catheterization and angiographicstudy. For each patient, the ECG tracing had been analyzedfor rhythm, p-wave, P-R interval, QRS axis, duration andT-wave in V1 and any chamber enlargement.Results: The ECG analysis revealed that all patients hadsinus rhythm, normal P-R interval and normal p-waveduration and amplitude, and normal QRS duration. Allstudied patients had one criteria of RVH and 95% of themhad two or more of such criteria.Conclusion: we found that in the absence of RVHcriteria, the diagnosis of TOF is unlikely and the present ofnorthwest axis should indicate canal type VSD